2021
DOI: 10.1111/cbdd.13849
|View full text |Cite
|
Sign up to set email alerts
|

Multiple interactions between melatonin and non‐coding RNAs in cancer biology

Abstract: The melatonin hormone secreted by the pineal gland is involved in physiological functions such as growth and maturation, circadian cycles, and biological activities including antioxidants, anti‐tumor, and anti‐ischemia. Melatonin not only interacts with proteins but also has functional effects on regulatory RNAs such as long non‐coding RNAs (lncRNAs) and microRNAs (miRNAs). In this study, we overview various physiological and pathological conditions affecting melatonin through lncRNA and miRNA. The information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 166 publications
0
5
0
Order By: Relevance
“…In addition, the coding-non-coding RNA network can also be perturbed by lncRNAs and circRNAs via acting as miRNA sponges, implicating that isomiR-mediated ceRNA network may be critical in the Notch pathway. Indeed, ncRNAs have been widely considered as crucial RNAs in cancer biology [74] , [75] , [76] , and ncRNA-based therapeutics have provided a new insight for cancer treatment that can facilitate better design of personalized therapeutics. More studies should focus on the detailed interaction mechanism among diverse RNAs and caused multiple cross-talks among diverse biological pathways, which may be quite important to explore the mechanisms of tumorigenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the coding-non-coding RNA network can also be perturbed by lncRNAs and circRNAs via acting as miRNA sponges, implicating that isomiR-mediated ceRNA network may be critical in the Notch pathway. Indeed, ncRNAs have been widely considered as crucial RNAs in cancer biology [74] , [75] , [76] , and ncRNA-based therapeutics have provided a new insight for cancer treatment that can facilitate better design of personalized therapeutics. More studies should focus on the detailed interaction mechanism among diverse RNAs and caused multiple cross-talks among diverse biological pathways, which may be quite important to explore the mechanisms of tumorigenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, melatonin (MT), an endogenous indole hormone that exists in many organisms, such as bacteria, fungi, and mammals, possesses many biological activities, including tissue repair promotion, immunoregulation, antioxidant activity, and anti-tumor effects. 20,21 Thus, CMCS/PDA/ MT (CPM) composite hydrogels would be great candidates for the potential management of periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are more than 200 nucleotide RNA molecules (Kirk et al, 2018). Recently, more and more evidence demonstrated that lncRNAs are engaged in multiple biological processes, containing cell proliferation, apoptosis, differentiation, development, and immune responses (Maleki et al, 2021). DNAJC3‐AS1, an oncogenic lncRNA, is characterized by various types of cancers (R. Liang et al, 2019; Na et al, 2021; Tang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%